Differences in Temporal Volume between Males and Females and the Influence of Age and BMI: A Cross-Sectional CT-Imaging Study - Nikolis, Andreas; Frank, Konstantin; Guryanov, Robert; Gombolevskiy, Victor; Morozov, Sergey; Makhmud, Kamal; Chernina, Valeria; Gotkin, Robert H.; Green, Jeremy Blair; Cotofana, Sebastian (Facial Plastic Surgery, 2021)
Background The temple has been identified as one of the most compelling facial regions in which to seek aesthetic improvement—both locally and in the entire face—when injecting soft tissue fillers.Objective The objective of this study is to identify influences of age, gender, and body mass index (BMI) on temporal parameters to better understand clinical observations and to identify optimal treatment strategies for treating temporal hollowing.Methods The sample consisted of 28 male and 30 female individuals with a median age of 53 (34) years and a median BMI of 27.00 (6.94) kg/m2. The surface area of temporal skin, the surface area of temporal bones, and the temporal soft tissue volume were measured utilizing postprocessed computed tomography (CT) images via the Hausdorff minimal distance algorithm. Differences between the investigated participants related to age, BMI, and gender were calculated.Results Median skin surface area was greater in males compared with females 5,100.5 (708) mm2 versus 4,208.5 (893) mm2 (p < 0.001) as was the median bone surface area 5,329 (690) mm2 versus 4,477 (888) mm2 (p < 0.001). Males had on average 11.04 mL greater temporal soft tissue volume compared with age and BMI-matched females with p < 0.001. Comparing the volume between premenopausal versus postmenopausal females, the median temporal soft tissue volume was 46.63 mL (11.94) versus 40.32 mL (5.69) (p = 0.014).Conclusion The results of this cross-sectional CT imaging study confirmed previous clinical and anatomical observations and added numerical evidence to those observations for a better clinical integration of the data.
Keywords: temporal fossa; temple; facial anatomy; soft tissue filler; volume augmentation